2011
DOI: 10.1111/j.1399-0012.2010.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the use of caspofungin in recipients of liver transplant with a modified high index of suspicion for fungal infection. A critical review of mortality, acute cellular rejection, infections, and changes in the liver function tests while on caspofungin

Abstract: This study is a retrospective analysis of death, adverse events (AE), fungal infections, and hepatic function among recipients of liver transplantation at high risk of fungal infection who received prophylactic treatment with caspofungin. After reviewing data of 105 patients who had received isolated liver transplant between January 2003 and April 2007, we identified and analyzed 82 high-risk patients. Post-transplant patients at high risk for fungal infection are commonly defined by the presence of at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Fungal infection is not uncommon after LT. Some studies have demonstrated that the incidence of fungal infection in LT recipients ranged from 16% to 42% (22,23). Castaldo et al (24) reported that the incidence of fungal infection after LT was 25.3% in 178 adult recipients, and 7.3% of adult recipients died of fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infection is not uncommon after LT. Some studies have demonstrated that the incidence of fungal infection in LT recipients ranged from 16% to 42% (22,23). Castaldo et al (24) reported that the incidence of fungal infection after LT was 25.3% in 178 adult recipients, and 7.3% of adult recipients died of fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…In LT, caspofungin is associated with a significantly higher risk of adverse events, especially acute renal failure ( p = 0.001), even though it does not carry an apparent increase in the risk of death or acute cellular rejection in LT [20]. Thus, voriconazole is the preferred antifungal therapy in SOT, regardless of possible influence in the tacrolimus metabolism in human liver microsomes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Echinocandins have been used safely in patients with preexisting hepatic impairment, namely, caspofungin in patients with chronic liver disease and postliver transplantation. Micafungin and anidulafungin have been used in patients with hepatic impairment; no worsening of the disease was observed [59, 60]. …”
Section: Discussionmentioning
confidence: 99%